First! Cultural circulation in the age of recursivity. (February 2017) - Powers, Devon
This article develops a cultural theory of firstness and argues for its importance in understanding contemporary cultural circulation. It argues that firstness is a metaculture that plays a role in making culture circulation faster, more reliant on quantification, and more promotional. After drawing support from philosophical, historical, and theoretical understandings of firstness, the article pays particular attention to the cases of web-based comment threads and music blogs to showcase how the competition to be first is central to the cultural ecosystem, especially but not only online. The conclusion suggests how firstness might be indicative of a recursive cultural mode.